Continuous Auditing Paradigma Baru dalam Pengauditan - Ferry Sihaloho (Universitas Kristen Maranatha, 2005)
One of the advanced information system that can produce financial statement in timely manner is the Real Time Accounting System in which will produce financial information without audit trail. Audit trails were common problem in recently audit practice because of the advanced information systemnot produce it. Auditor should change old paradigm in auditing related to audit procedures that used to examine the Accounting Information System by which can produce audit trail. Auditor must focus on program’s application system through the computer. Continuous Auditing could used by auditor as anaudit technique to ensure that the program’s application system well-to-do processing transaction with high validity and reliability. Although audit firm must prepare infiastructure and data standardization, but they can obtain benefit related to audit cost (i. e. reduce the operational audit cost and audittime). The effectiveness and efliciency of audit ’s effort will result in the competitive audit fees that can be offered by auditors to their clients.Kata kunci: Real Time Accounting, Continuous Auditing, fee audit.